Analysis of the trend in the number of Slovenians in Montenegro 1921 - 2021 and their organisation - Tomažič, Dušan (Journal for Geography, 2022)
Analysis of the trend in the number of Slovenians in Montenegro 1921 - 2021 and their organisationThere are a small number of Slovenians living in Montenegro, but they are still very interesting to study. The first census of the population of Montenegro was carried out in 1879 during the reign of Prince Nikola. The first fairly accurate census data dates back to 1909, while later, modern censuses were carried out in three state-territorial contexts. Six censuses were conducted during the Kingdom of the SHS (1921 and 1931), six censuses during the SFRY (1948-1991) and two censuses during the independent Republic of Montenegro (2003 and 2011). The Slovenian population was already visible in the 1921 census, when 55 persons identified themselves as Slovenes. The first census in modern Montenegro counted 415 Slovenians, for whom demographic trends are desperate and represent a biological depopulation.  In the last census in 2011, even fewer persons declared themselves Slovenes, 354, and the average age rose to 53.2 years. The present work provides a basic demographic analysis of Slovenians in the Republic of Montenegro and how the change in the country's legal status has affected the development of the Slovenian population and its organisation in the new state.
Keywords: Age; census; education; gender; Montenegro; mother tongue; Slovenians